A Novel Labview Based Anti Islanding Detection Method for Grid Connected PV Systems - Bayrak, Gokay; Cebeci, Mehmet (Ieee, 2013)
Renewable energy sources (RES) have been come into prominence all over the world and solar energy is the most developed energy sources in RES. Photovoltaic (PV) systems have been used with related to solar energy is one of the most preferred systems thanks to their improved technology and user-friendly applications. Grid connected PV systems also have been developed all over the world and as long as they have been become widespread there have been some drawbacks about connecting them to the electrical grid. One of the drawbacks of connecting PV systems to the grid and maybe the most important one is unintentional islanding condition. Islanding can be dangerous for utility workers and damage utility equipment so anti islanding is a crucial subject for grid connected PV systems. There have been many anti islanding detection methods in the literature but most of them have some boundaries related with local load and PV inverter. In this application study, a novel Labview based islanding detection method for grid connected PV systems was proposed. For this aim, 1.2 kWp grid connected PV system installed in laboratory at Firat University Electrical and Electronics Engineering Department was used and a real time controller was developed with Labview and its useful tools. Proposed method is not inverter resident so it can be easily adapted to the grid connected PV systems. The results obtained from the proposed real time anti islanding detection method shows that it is reliable, robust and independent from load and inverter. Non detection zone (NDZ) is almost zero and it has a significant short response time according to IEEE 929-2000. In this study, all the experimental results were explained in detail and compared with simulation results developed by Matlab Simulink All obtained results correspond with both simulation and experimental results. Proposed method is effective and applicable to all grid connected PV systems independently from load and PV inverter and it presents a realistic solution to islanding.
International Conference on Renewable Energy Research and Applications (ICRERA) -- OCT 20-23, 2013 -- Madrid, SPAIN
Keywords: islanding detection; grid connected PV system; solar energy